The relationship between green supply chain management and performance: a meta-analysis of empirical evidences in Asian emerging economics - Geng, Ruoqi; Mansouri, S. Afshin; Aktas, Emel (Elsevier, 2016)
The purpose of this study is to understand the relationship between green supply chain management (GSCM) practices and firm performance in the manufacturing sector in Asian emerging economies (AEE) based on empirical evidence. Through a systematic literature review, we identified 50 articles that surveyed 11,127 manufacturing companies in the AEE and were published between 1996 and 2015. Subsequently, a conceptual framework was developed and analyzed through a meta-analysis of 130 effects from 25,680 effect sizes. The findings revealed that the GSCM practices lead to better performance in four aspects: economic, environmental, operational, and social performance. Moreover, the results indicate that industry type, firm size, ISO certification, and export orientation moderate several of the GSCM practice-performance relationships. Moreover, the findings of this research help managers and policy makers to have more confidence in the adoption of GSCM practices to improve firm performance. Such results also help researchers to better channel their efforts in studying the GSCM practices in Asian emerging economies. In addition, as meta-analysis has not been widely used in the supply chain management literature, our study is an important step in maturing the academic field by adopting this technique for confirming GSCM practice-performance relationships in the manufacturing sector of Asian emerging economies.
Keywords: Green supply chain management; Asian emerging economies; Manufacturing sector; Performance